FAKTOR-FAKTOR YANG DIPERTIMBANGKAN KONSUMEN MENGGUNAKAN JASA BENGKEL MOBIL â€œSINAR KARYAâ€ DI KOTA PALU - HAQ, BUSTANUL (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2019)
This study aims to describe the factors that consumers consider using the "Sinar Karya" Car Repair Service in Palu City. The problems raised in this study are what factors are considered by consumers using the services of the "Sinar Karya" Car Repair Shop in Palu City. The sample of this study were 96 respondents, namely consumers who use the services of "Sinar Karya" Car Repair Shop in Palu City. This study uses explorative research type, using data collection methods in the form of observation, interviews, documentation, questionnaires and literature study. Instrument testing uses validity and reliability tests. The results of factor analysis that consumers consider using the "Sinar Karya" Car Repair Service in Palu City concludes that there are 4 (four) factors that consumers consider using the "Sinar Karya" Car Repair Service in Palu City. The four factors are the factors of people and service, place factors, proximity factors, and characteristic factors. Overall, the four factors mentioned, have been empirically proven are the factors that are considered by consumers using the Motorbike's "Sinar Karya" Car Repair Service in the City of Palu